2016
DOI: 10.2147/ijn.s122726
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical evaluation of aminoclay as an effective protectant for protein stabilization during freeze-drying and storage

Abstract: This study aimed to evaluate aminoclay (3-aminopropyl-functionalized magnesium phyllosilicate) as an effective protectant for the stabilization of protein formulation in freeze-drying. Bovine serum albumin (BSA), as a model protein, was freeze-dried with aminoclay at various concentrations, and the effects of aminoclay on the structural stability of proteins were compared with those of the conventional stabilizers. The structural characteristics of the protein were determined by size exclusion chromatography (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Furthermore, these results were confirmed by deconvoluted amide I region of FT-IR spectra and the secondary structure contents of insulin released from nanoparticles (Additional file 1 : Figure S2). This result suggests that the aminoclay-based core complex can serve as an effective support matrix to maintain the native structure of immobilized proteins [ 22 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these results were confirmed by deconvoluted amide I region of FT-IR spectra and the secondary structure contents of insulin released from nanoparticles (Additional file 1 : Figure S2). This result suggests that the aminoclay-based core complex can serve as an effective support matrix to maintain the native structure of immobilized proteins [ 22 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has demonstrated that the formation of the drug-clay complex improved the water solubility and bioavailability of drugs [23]. Aminoclay has several advantages as a drug carrier, including (i) easy preparation of a nanocomplex via spontaneous co-assembly with a diverse range of drugs, (ii) an effective support matrix to maintain the native structure of immobilized proteins, (iii) a reversible effect on tight junction opening, and (iv) low cytotoxicity [23][24][25][26][27][28][29]. Han et al [28] demonstrated that aminoclay had little cytotoxicity at concentrations of up to 500 μg/mL and did not induce apoptosis at concentrations of up to 1000 μg/mL.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the long-term stability of the freeze-drying method might still be limited, especially at high temperatures. These problems could be minimized by choosing the optimal pH and remaining moisture content, and more importantly, by the addition of stabilizers that might prevent tissue freezing and cell destruction during the cooling processes [23].…”
Section: The Homogeneity and Stability Of Samples Produced Bymentioning
confidence: 99%
“…However, some proteins could undergo structural changes during the VFD process. For instance, Song et al reported that the structure of bovine serum albumin changed during the VFD process [9]. A limited number of potentials for biopharmaceuticals might undergo inactivation, denaturation, and other reactions during the fabricating process [10].…”
Section: Introductionmentioning
confidence: 99%